Epinephrine Auto-Injectors for Anaphylaxis Treatment in the School Setting: A Discussion Paper - Abigail Tarr Cooke AAS, RDH; Robin Meize-Grochowski PhD, RN, CNE (SAGE Publishing, 2019)
Introduction: Anaphylaxis is a serious, life-threatening systemic allergic reaction that may occur in individuals not previously diagnosed with an allergy. Emergency first-line treatment of choice for acute anaphylaxis is intramuscular administration of epinephrine via an auto-injector. In the school setting, students with known allergies typically keep or carry an epinephrine auto-injector (EAI). For students who do not have a known allergy or for those whose personal EAIs are unavailable, an anaphylactic event could have serious adverse outcomes if an EAI is not available via an undesignated stock supply in the school. Methods: We searched the published literature from 2000 through 2018 in CINAHL, MEDLINE, and PubMed using the following search terms: anaphylaxis , school setting , epinephrine auto-injector , and food allergies . Throughout this article, undesignated stock EAIs, stock EAIs, EAI stock, and open-order EAIs are used interchangeably. Conclusion: Anaphylaxis is increasing worldwide as the incidence of food allergies increases. Although stock EAIs for students in schools can have important benefits, the availability of EAIs in the school setting is limited. Barriers to undesignated stock EAIs include the lengthy administrative process for developing school policies and protocols; gaps in nurses' self-perceived knowledge versus objective knowledge on the topic of anaphylaxis; limited resources in many school districts; and complex role demands, lack of confidence in trained staff, or insufficient school nurse staffing. It is important that epinephrine be readily available in schools. Barriers to facilitating stock EAIs include those that can be addressed directly by nurses and those that may require policy changes. Nurses, particularly those working in school settings or pediatrics, could take the lead in discussions about the benefits of stock EAIs in schools, advocating for policy changes as warranted. Fully informed nurses can be better prepared to serve as advocates in ensuring that EAIs are available in school settings.